Mount Kare gold rush : Papua New Guinea 1988 - 1994 - Henton, David; Flower, Andi. (Cotton Tree, Qld. : Mt Kare Gold Rush, 2007)
"History and political intrigue of the Mt Kare gold rush. Papua New Guinea 1988 - 1994"--Provided by publisher.
Keywords: Gold mines and mining -- Papua New Guinea -- Porgera Region -- History; Porgera Region (Papua New Guinea) -- History